Incentive Management, Corporate Social Responsibility, Political Connections, and Firm Value: The Moderating Role of Corporate Governance - Nurlaela, Siti; ., Rahmawati; Widagdo, Ari Kuncara; Joseph, Corina; Amperawati, Endang Dwi; ., Kiswanto (Journal of Ecohumanism, 2024)
The first aim of this paper is to examine the relationship between incentive management, corporate social responsibility, political connections, and firm value in the mining industry using the agency theory. The second aim is to examine corporate governance's moderating role in the relationship between incentive management, corporate social responsibility, political connections, and firm value. This research uses Moderated Regression Analysis (MRA) to realize the objectives. This study finds a relationship between incentive management, corporate social responsibility, political connections, and firm value. It also finds that corporate governance moderates the relationship between incentive management, corporate social responsibility, political connections, and firm value. Corporate governance plays a role in helping to reduce agency problems and strengthen corporate supervision. The results of this study provide theoretical contributions to the literature on the development of corporate governance and capital markets, especially in investment decision-making. The findings of this study can be used as a consideration for policies related to regulations in the management of incentives management, corporate social responsibility, corporate governance, and corporate value.